Gas and nuclear power as transition technologies: What does this mean for investments - Rainer Haselmann; Sebastian Steuer; Tobias Tröger (EconPol Forum, 2023)
So far, the applications of the Taxonomy are purely for transparency and disclosure purposes. Professional investors and regulators instead rely on more advanced and context-specific metrics, such as their own ESG methodologies and cockpits. Therefore, the controversial Taxonomy classification of gas and nuclear power will not have a major impact. Green finance policies are no substitute for restrictive environmental regulations such as cap-and-trade schemes or outright prohibitions of certain activities.
Keywords: 330